A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters. Issue 1 (October 2016) - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf
Abstract: This work employs a fuzzy finite element method (FFEM) in order to characterize the non‐statistical properties based on the possibility theory [2]. A linear elastic body with fuzzy input material parameters Young's modulusE and Poisson's ratioν is studied. To this end, the fuzzy parameters are represented by possibility distributions generated from sparse experimental data. A computational approach involving the α‐level discretization technique [4] is used in order to calculate the possibility of the system response. Finally, our method is applied in a numerical example. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)